Pyramidal tract side effects induced by deep brain stimulation of the subthalamic nucleus. Issue 7 (10th October 2007) - Tommasi, G; Krack, P; Fraix, V; Le Bas, J-F; Chabardes, S; Benabid, A-L; Pollak, P
Abstract : Objective: To study the pyramidal tract side effects (PTSEs) induced by the spread of current from the subthalamic nucleus (STN) to the pyramidal tract (PT), in patients with parkinsonism undergoing STN stimulation. Methods: 14 patients bilaterally implanted with tetrapolar electrodes were assessed. For each side separately, the threshold of adverse effects induced by monopolar stimulation delivered by the chronically used contact was detected. The voltage was progressively increased until the patient experienced discomfort. All the PTSEs induced at 130 Hz (high-frequency stimulation (HFS)) and 2 or 3 Hz (low-frequency stimulation (LFS)) were videotaped. By superimposing the preoperative and postoperative MR images, the minimum distance (R) from the centre of the used contact to the medial border of the PT were measured. Results: The progressive increase in voltage at HFS induced tonic motor contractions, mainly located in the face, in 27/28 electrodes. LFS induced synchronous rhythmic myoclonus in the same territory. PTSEs induced at threshold voltage by HFS were observed in the upper face at 13/28 electrodes (bilaterally in six cases) and in the contralateral lower face at five electrodes. A positive correlation was found between the stimulus intensity capable of eliciting motor contractions at HFS and R. Conclusions: HFS of the STN preferentially activates the corticobulbar tract over the corticospinal tract. Therefore, cranial motor contractions need to be looked for during electrical parameter setting. The positive correlation between the electrical intensity threshold for PTSEs and R reflects the need for millimetre accuracy in electrode positioning.